The effects of implementing iso 42001 AI management systems into autonomous maritime operations - Eslam Abdelghany E. Mohamed (Maritime Research and Technology)
The integration of Artificial Intelligence (AI) in autonomous maritime operations has significant potential to alter dramatically the industry by enhancing operational efficiency, safety, and compliance. However, the lack of a structured framework to manage AI systems and autonomous maritime operations presents a critical gap, particularly in addressing risks such as inaccuracy, cybersecurity vulnerabilities, and regulatory compliance challenges. This research aims to bridge this gap by investigating the application of International Organization for Standardization (ISO) 42001:2023 standards, focusing on the selection and implementation of specific controls from Annex A. This research engages an approach of scenario studies focusing on a particular case study during an ISO 42001:2023 requirements course conducted by Det Norske Veritas (DNV) at the Arab Academy for Science, Technology and Maritime Transport (AASTMT). The selected controls are assessed on their categorization, and their relevance to the maritime operations, and using the Plan-Do-Check-Act (PDCA) model, the research assesses the adequacy of those controls in achieving improvements in governance, risk management, and operational efficiency in autonomous maritime operations. Key findings demonstrate that ISO 42001:2023 is appropriate in mitigating AI-related risks while ensuring transparency, accountability, and compliance. The research underscores the selected controls’ usefulness as regards some critical issues in guidance, decision, and resource management. These outcomes considerably affect how AI management systems can be integrated into the maritime transport industry and serve as a basis for more extensive harmonization and incorporation with the international organization for standardization.   Received on: 10 March 2025 Accepted on: 01 June 2025 Published on: 03 June 2025